La institucionalización de la ciencia política en Chile y América Latina: una mirada desde el Sur - Altman, David (Revista de Ciencia Política, 2019)
This introduction does not try to be more than a first approach on the state–of–the–art of political science in the continent. It is argued that Latin American political science must build university institutions that emphasize clear rules and defined criteria that stimulate meritocracy as their leit motif. For meritocracy to exist, criteria are necessarily to account for research and teaching productivity. Evidently, the establishment of these criteria is fundamental at the time of the evaluations. Currently, the continent shows enormous variations in the minimally necessary conditions for the institutionalization of the discipline. In some countriesnot even a degree in political science at undergraduate or graduated can be obtained. In others, less than five doctors in political science are currently working at the university realm. The urgent necessity of professionalization continues being an important subject to consider.